Reliability of Questionnaires to Assess the Healthy Eating and Activity Environment of a Child's Home and School. (1st July 2013) - Wilson, Annabelle; Magarey, Anthea; Mastersson, Nadia
Abstract : Childhood overweight and obesity are a growing concern globally, and environments, including the home and school, can contribute to this epidemic. This paper assesses the reliability of two questionnaires (parent and teacher) used in the evaluation of a community-based childhood obesity prevention intervention, the eat well be active (ewba) Community Programs. Parents and teachers were recruited from two primary schools and they completed the same questionnaire twice in 2008 and 2009. Data from both questionnaires were classified into outcomes relevant to healthy eating and activity, and target outcomes, based on the goals of the ewba Community Programs, were identified. Fourteen and 12 outcomes were developed from the parent and teacher questionnaires, respectively. Sixty parents and 28 teachers participated in the reliability study. Intraclass correlation coefficients for outcomes ranged from 0.37 to 0.92 (parent) (P < 0.05 ) and from 0.42 to 0.86 (teacher) (P < 0.05 ). Internal consistency, measured by Cronbach's alpha, of teacher scores ranged from 0.11 to 0.91 and 0.13 to 0.78 for scores from the parent questionnaire. The parent and teacher questionnaires are moderately reliable tools for simultaneously assessing child intakes, environments, attitudes, and knowledge associated with healthy eating and physical activity in the home and school and may be useful for evaluation of similar programs.